The heiress ebook - Hawkins, Rachel (2024)
NATIONAL BESTSELLER A January 2024 Indie Next Pick and LibraryReads Pick " The reigning queen of the Gothic thriller." — Entertainment Weekly THERE'S NOTHING AS GOOD AS THE RICH GONE BAD. When Ruby McTavish Callahan Woodward Miller Kenmore dies, she's not only North Carolina's richest woman, she's also its most notorious. The victim of a famous kidnapping as a child and a widow four times over, Ruby ruled the tiny town of Tavistock from Ashby House, her family's estate high in the Blue Ridge Mountains. But in the aftermath of her death, her adopted son, Camden, wants little to do with the house or the money—and even less to do with the surviving McTavishes. Instead, he rejects his inheritance, settling into a normal life as an English teacher in Colorado and marrying Jules, a woman just as eager to escape her own messy past. Ten years later, his uncle's death pulls Cam and Jules back into the family fold at Ashby House. Its views are just as stunning as ever, its rooms just as elegant, but the legacy of Ruby is inescapable. And as Ashby House tightens its grip on Jules and Camden, questions about the infamous heiress come to light. Was there any truth to the persistent rumors following her disappearance as a girl? What really happened to those four husbands, who all died under mysterious circumstances? And why did she adopt Cam in the first place? Soon, Jules and Cam realize that an inheritance can entail far more than what's written in a will––and that the bonds of family stretch far beyond the grave.